2022
DOI: 10.3390/ijms23158797
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the First Highly Selective Antagonist of the GluK3 Kainate Receptor Subtype

Abstract: Kainate receptors belong to the family of glutamate receptors ion channels, which are responsible for the majority of rapid excitatory synaptic transmission in the central nervous system. The therapeutic potential of kainate receptors is still poorly understood, which is also due to the lack of potent and subunit-selective pharmacological tools. In search of selective ligands for the GluK3 kainate receptor subtype, a series of quinoxaline-2,3-dione analogues was synthesized and pharmacologically characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The introduction to this position of a large bicyclic substituent linked by a triple bond to the quinoxalinedione core (17,18) appeared to be an important structural modification that clearly affected the binding to the GluK3 subunit, resulting in the compound 17 with a pronounced preference for GluK3 and submicromolar GluK3 affinity (K i = 0.253 µM, Table 2). In fact, a 400-fold selectivity for GluK3 over the subtypes GluK1, GluK2, GluK5, and GluA2, reported for this analogue, has been a unique KA receptor affinity profile among all structures described to date [97]. On the other hand, the most active compound in this series, 18, showed a weak selectivity profile but a high affinity at the homomeric receptors GluK1, GluK3, and also GluK2, thus presenting one of the highest GluK2-affinity values among the quinoxalinedione-based ligands reported so far (Table 2).…”
Section: Competitive Antagonists Of the Kainate Receptorsmentioning
confidence: 90%
See 1 more Smart Citation
“…The introduction to this position of a large bicyclic substituent linked by a triple bond to the quinoxalinedione core (17,18) appeared to be an important structural modification that clearly affected the binding to the GluK3 subunit, resulting in the compound 17 with a pronounced preference for GluK3 and submicromolar GluK3 affinity (K i = 0.253 µM, Table 2). In fact, a 400-fold selectivity for GluK3 over the subtypes GluK1, GluK2, GluK5, and GluA2, reported for this analogue, has been a unique KA receptor affinity profile among all structures described to date [97]. On the other hand, the most active compound in this series, 18, showed a weak selectivity profile but a high affinity at the homomeric receptors GluK1, GluK3, and also GluK2, thus presenting one of the highest GluK2-affinity values among the quinoxalinedione-based ligands reported so far (Table 2).…”
Section: Competitive Antagonists Of the Kainate Receptorsmentioning
confidence: 90%
“…The N1-benzamide analogue 16 with an unsubstituted 7-position of the quinoxalinedione scaffold and possessing a phenylethynyl moiety at position 6 (Figure 3), demonstrated an interesting selectivity profile showing approximately a 30-fold preference for the GluK3 homomeric receptors over the subtypes GluK1 and GluK2 [92]. Following 16 as the lead structure, a series of quinoxaline-2,3-dione analogues with an ethynyl substituent at the 6position has recently been presented [97]. The introduction to this position of a large bicyclic substituent linked by a triple bond to the quinoxalinedione core (17,18) appeared to be an important structural modification that clearly affected the binding to the GluK3 subunit, resulting in the compound 17 with a pronounced preference for GluK3 and submicromolar GluK3 affinity (K i = 0.253 µM, Table 2).…”
Section: Competitive Antagonists Of the Kainate Receptorsmentioning
confidence: 99%
“…Since the crystal structure of GluK3-LBD co-crystallized with a competitive antagonist has not currently been developed, a recently established homology model was used for the docking studies. [9] The model was constructed using the GluK1-LBD Xray structure (PDB ID: 6SBT) and refined by an induced fit docking procedure using N-(7-fluoro-2,3-dioxo-6-(trifluoromethyl)-3,4-dihydroquinoxalin-1(2H)-yl)-2-hydroxy-benzamide (1) as the docked ligand.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…[8a] Recently, the extended series of GluK3-selective quinoxalinedione derivatives with a similar structure has been reported. [9] Furthermore, analysis of the X-ray complexes of the GluK1 ligand binding domain (LBD) with bound 1 or 4 showed that both compounds adopt a similar binding mode seen also in the case of other quinoxalinedione-based AMPA/KA antagonists, and the benzamide substituent at the N1-position is located on the edge of the binding pocket. For this part of the molecule only π-π stacking interaction with the protein backbone of Gly688-er689 was observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation